2014
DOI: 10.1002/mbo3.187
|View full text |Cite
|
Sign up to set email alerts
|

The biofilm matrix destabilizers, EDTA and DNaseI, enhance the susceptibility of nontypeable Hemophilus influenzae biofilms to treatment with ampicillin and ciprofloxacin

Abstract: Nontypeable Hemophilus influenzae (NTHi) is a Gram-negative bacterial pathogen that causes chronic biofilm infections of the ears and airways. The biofilm matrix provides structural integrity to the biofilm and protects biofilm cells from antibiotic exposure by reducing penetration of antimicrobial compounds into the biofilm. Extracellular DNA (eDNA) has been found to be a major matrix component of biofilms formed by many species of Gram-positive and Gram-negative bacteria, including NTHi. Interestingly, the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
84
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 58 publications
3
84
0
Order By: Relevance
“…Indeed, Lambert et al [33] showed that EDTA had a synergistic effect with other antimicrobial agents. DNaseI and EDTA were used in combination with ampicillin and ciprofloxacin to reduce Haemophilus influenzae biofilm [34]. On the other hand, a study on otopathogenic strains of PA revealed that while EDTA delayed biofilm development and could inhibit growth of planktonic PA, it did not suppress biofilm formation in all the otopathogenic strains of PA [35].…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, Lambert et al [33] showed that EDTA had a synergistic effect with other antimicrobial agents. DNaseI and EDTA were used in combination with ampicillin and ciprofloxacin to reduce Haemophilus influenzae biofilm [34]. On the other hand, a study on otopathogenic strains of PA revealed that while EDTA delayed biofilm development and could inhibit growth of planktonic PA, it did not suppress biofilm formation in all the otopathogenic strains of PA [35].…”
Section: Discussionmentioning
confidence: 98%
“…The EM can bind various antimicrobials with its versatile components. For example, eDNA interacts with aminoglycosides, thereby protecting P. aeruginosa biofilm-associated cells [33]; sub-inhibitory concentrations of penicillin augment the production of all EM components of Actinobacillus pleuropneumoniae [34]; and the treatment of Haemophilus influenzae biofilms with DNase I makes the cells more sensitive to ampicillin and ciprofloxacin [35]. Deletion of hofQ decreased the amount of eDNA while increasing the susceptibility to the tested β-lactams, supporting the hypothesis that eDNA can sequester and protect biofilm-associated cells from the activity of β-lactams.…”
Section: Discussionmentioning
confidence: 99%
“…For example, DNase I increases the susceptibility of nontypeable Haemophilus influenzae to ampicillin and ciprofloxacin and partially sensitises biofilm cells of Mycobacterium tuberculosis to isoniazid [51,52]. Vancomycin binds 100 times more tightly to DNA than to its cellular target, the dAla-d-Ala C terminus of the peptidoglycan pentapeptide, and eDNA protects Staphylococcus epidermidis biofilms from vancomycin [53].…”
Section: Protection Against Antimicrobial Agentsmentioning
confidence: 98%